Medical image processing - Chen, Guanyu (2019)
Medical image processing techniques help make important decisions in disease diagnosis and prescription of medical treatment in various clinical settings. When used in conjunction with medical professionals, such techniques can improve detection outcomes. Image segmentation is one such technique used to deal with medical images. The medical image processing techniques involving image segmentation are used mainly to delineate organs or anatomical structures of interest from medical images before the diagnosis of various disease is made. Lung segmentation, which involves identifying the boundaries of lungs on computed tomographic (CT) images, is a crucial step in the diagnosis of many lung diseases. This report will discuss the use of active contours in performing lung segmentation on CT images as well as other areas in which image segmentation is performed.